Pengaruh Model Pembelajaran Kooperatif Tipe NHT (Numbered Head Together) Terhadap Hasil Belajar Teknik Dasar Passing Permainan Bola Voli pada Siswa Kelas X SMA Negeri 1 Mendoyo - Maharani, Ni Putu Icha; Ilmawan, Anggo Widcaksana; Andika, I Gede Angga (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to analyze the effect of the Numbered Heads Together (NHT) cooperative learning model on the learning outcomes of basic passing techniques in volleyball among grade X students of SMA Negeri 1 Mendoyo. This study uses a quantitative approach with a quasi-experimental method and a non-randomized control group pretest-posttest design. The research sample consists of two classes, namely the experimental class and the control class, each comprising 33 students selected randomly. The experimental class receives treatment with the NHT learning model, while the control class follows the conventional learning model. The data collection instrument is conducted through practical tests of basic underhand and overhand passing techniques in volleyball. The data were analyzed using normality tests, homogeneity, t-tests, and effectiveness calculations. The research results showed a significant improvement in student learning outcomes in the experimental group compared to the control class. The average lower passing score in the experimental group was 81.12 and the upper passing score was 81.33, which is much higher compared to the control class that obtained average scores of 44.97 and 39.76, respectively. The significance value of the t-test is 0.000 (p < 0.05), indicating that the NHT learning model has a significant impact on improving learning outcomes.